Translocation and accumulation of boron in roots and shoots of plants grown in soils of low B concentration in Turkey’s Keban Pb-Zn mining area - Şaşmaz, Ahmet (My University, 2008)
Boron (B) concentrations were investigated in both shoots and roots of Euphorbia macroclada, Verbascum cheiranthifolium, and Astragalus gummifer grown in soil of the Keban, Turkey, Lead–zinc–copper–fluoride mining area, which has an arid climate. Soil B concentrations were also investigated. Plants and their associated soil samples were collected and analyzed by Inductively Coupled Plasma–Mass Spectrometry (ICP-MS). Total B concentrations of soils in the study area were very low (mean: 4.97 mg kg?1) as compared with those in surface soils in other countries. Boron concentrations of plant organs were several times higher than those in their associated soils. The mean values of B concentrations in roots of E. macroclada, V. cheiranthifolium, and A. gummifer were 25, 70, and 69 mg kg?1, respectively, while those in shoots were 75, 115, and 77 mg kg?1, respectively. Results indicate that roots and shoots of plants grown in soils with low B concentrations can be used both as biomonitors for environmental contamination and biogeochemical indicators for B.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Boron (B) uptake; Euphorbia; Verbascum; Astragalus; Soil; Ttranslocation factor; Enrichment coefficient